The role of major and minor structural proteins of porcine reproductive and respiratory syndrome virus in induction of protective immunity - Li, Dan; Zhu, Laixu; Cui, Chenchen; Wu, Zhenchun; Qing, Pengkai; Zhou, Qiongqiong; Gao, Peng; Zhang, Yongning; Zhou, Lei; Ge, Xinna; Guo, Xin; Han, Jun; et al. (Frontiers in Microbiology, 2025)
IntroductionPorcine reproductive and respiratory syndrome virus (PRRSV), an economically significant threat to the world pork production, is notoriously known for its heterogeneity, and therefore the current vaccines often fail to provide efficient cross-protection against diverse PRRSV strains.MethodsBy making chimeric viruses using HP-PRRSV-2 lineage 8 (JXwn06) and lineage 1 NADC30-like strains (CHsx1401) as model organisms, the recently results have shown that the viral structural protein-coding region is critical for induction of homologous immunity. In this study, the chimeric viruses were further constructed by exchanging the region coding for the minor (GP2/3/4) or major (GP5/M) structural proteins of JXwn06 on the backbone of CHsx1401 to generate two mutants CHsx1401-GP234JX and CHsx1401-GP5MJX.ResultsThe subsequent animal experiment showed that all three chimeras could confer good protective immunity against the lethal challenge by HP-PRRSV strain JXwn06, and the survived pigs had much lower lung lesions, faster viremia clearance, and lower viral tissue load. However, the exchange of SP region as a whole performed better than either GP2/3/4 or GP5/M region alone, as the pigs in the latter groups showed transient fever following challenge and higher viral load in certain tissues, highlighting a synergistic role. Interestingly, as compared to the group CHsx1401-GP234JX, the group CHsx1401-GP5MJX showed excellent viremia clearance, comparable to the SP group.DiscussionOur results in this report revealed the important role of ORFs2-4 and ORFs5-6 regions in induction of protective immunity and have important implications in understanding viral pathogenesis and further vaccine development.